FDI spillovers and time since foreign entry - Bruno Merlevede; Koen Schoors; Mariana Spatareanu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This study measures the effect of foreign direct investment (FDI) on the productivity of local firms. Unlike earlier studies, our empirical approach does not require that FDI manifests immediate or permanent effects. We find that foreign entry initially affects productivity of local competitors negatively, but is more than offset by a permanent positive effect on local competitors once majority-foreign-owned firms have been present for a while. The effect on the productivity of local suppliers, in contrast, is transient. The entry of majority-foreign-owned firms boosts productivity of local suppliers after a short adaption period, but then fades. The positive impact of minority-foreign-owned firms on local suppliers is immediate, but smaller and transient.
URN:NBN:fi:bof-201408072041
Keywords: F2; 330; FDI; spillovers; dynamics; timing